Pengaruh suhu pengeringan dan ukuran potongan terhadap karakteristik pengeringan nanas (Ananas comosus) - Hadijah Gajah; Misril Fuadi; Noor Azizah Binti Ahmad; Hairiyah Binti Mohamad (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2026)
Pineapple (Ananas comosus L. Merr.) is a tropical fruit with high economic value, but it has a short shelf life, requiring post-harvest processing to increase stability and added value. This study aimed to analyze the effect of drying temperature and slice size on the physical, chemical, and microbiological characteristics of pineapple powder. Pineapple variety MD2 was dried using a convection oven at 60°C and 70°C with slice sizes of 0.25 cm and 0.125 cm. The parameters observed included moisture content, water activity (a_w), pH, total soluble solids (TSS), color (L*, a*, b*), and microbiological quality. The results showed that increasing the drying temperature and reducing the slice size significantly reduced the moisture content and a_w value of pineapple powder. Treatment at 70°C with a slice size of 0.125 cm resulted in the lowest a_w value and the best microbiological stability. However, higher drying temperatures tended to decrease color brightness due to non-enzymatic browning. Overall, the combination of a temperature of 70°C and a cut size of 0.125 cm is the optimum condition for producing pineapple powder that is stable and safe for consumption, while still maintaining the quality of the product color.